2015
DOI: 10.5455/medscience.2015.04.8246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Practice of Antibiotic Prophylaxis in a State Hospital

Abstract: In terms of antibiotic prophylaxis in surgical patients, incorrect application in hospitals is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…For proper antibiotic prophylaxis, guidelines state that an antibiotic should be administered within one hour before the surgical incision, the correct antimicrobial agent should be given, and the duration of usage should not exceed 24 hours [2]. However, when the literature was examined, it has been shown that compliance with the surgical antibiotic prophylaxis guidelines is frequently not closely followed [3-5]. Due to the overuse of antibiotics and other drugs, there is a current policy toward "rational drug use" in Turkey, as in other parts of the globe, and substantial successful progress has been achieved [6].…”
Section: Introductionmentioning
confidence: 99%
“…For proper antibiotic prophylaxis, guidelines state that an antibiotic should be administered within one hour before the surgical incision, the correct antimicrobial agent should be given, and the duration of usage should not exceed 24 hours [2]. However, when the literature was examined, it has been shown that compliance with the surgical antibiotic prophylaxis guidelines is frequently not closely followed [3-5]. Due to the overuse of antibiotics and other drugs, there is a current policy toward "rational drug use" in Turkey, as in other parts of the globe, and substantial successful progress has been achieved [6].…”
Section: Introductionmentioning
confidence: 99%
“…For proper antibiotic prophylaxis, guidelines state that an antibiotic should be administered within one hour before the surgical incision, the correct antimicrobial agent should be given, and the duration of usage should not exceed 24 hours [2]. However, when the literature was examined, it has been shown that compliance with the surgical antibiotic prophylaxis guidelines is frequently not closely followed [3][4][5]. Due to the overuse of antibiotics and other drugs, there is a current policy toward "rational drug use" in Turkey, as in other parts of the globe, and substantial successful progress has been achieved [6].…”
Section: Introductionmentioning
confidence: 99%